Engineering Active Sites of Polyaniline for AlCl2+ Storage in an Aluminum‐Ion Battery. Issue 29 (20th May 2020) - Wang, Shuai; Huang, Shuo; Yao, Minjie; Zhang, Yan; Niu, Zhiqiang
Abstract: The reversible capacity of AlCl4 − intercalation/de‐intercalation in conventional cathodes of aluminum‐ion batteries (AIBs) is difficult to improve due to the large size of AlCl4 − anions. Therefore, it is highly desirable to realize the intercalation/de‐intercalation of smaller Al‐based ions. Here, we fabricated polyaniline/single‐walled carbon nanotubes (PANI/SWCNTs) composite films and protonated the PANI nanorods. The protonation endows PANI with more active sites and enhanced conductivity. Hyper self‐protonated PANI (PANI(H + )) exhibits reversible AlCl2 + intercalation/de‐intercalation during the discharge/charge process. As a result, the discharge capacity of the Al/PANI(H + ) battery is twice as high as that of the initial composite films. PANI(H + )@SWCNT electrodes also have a stable cycling life with only 0.003 % capacity decay per cycle over 8000 cycles. Owing to the excellent mechanical properties, PANI(H + )@SWCNT composite films can act as the electrodes of flexible AIBs. Abstract : Aluminum‐ion batteries : Composite films of polyaniline/single‐walled carbon nanotubes (PANI/SWCNTs) are produced for use as electrodes in aluminum‐ion batteries (AIBs). The protonation of PANI in PANI/SWCNTs enables reversible AlCl2 + intercalation/de‐intercalation in an Al/PANI(H + ) battery. PANI(H + )@SWCNT electrodes have a stable cycling life and owing to their mechanical stability, can also be used as electrodes of flexible AIBs.